Robust and cost-effective silver dendritic nanostructures for SERS-based trace detection of RDX and ammonium nitrate. Issue 73 (17th December 2020) - Vendamani, V. S.; Rao, S. V. S. Nageswara; Pathak, A. P.; Soma, Venugopal Rao
Abstract : We report the fabrication and performance evaluation of cost-effective, reproducible silver nanodendrite (AgND) substrates, possessing high-density trunks and branches, achieved by a simple electroless etching and used for the trace detection of RDX and Ammonium Nitrate. Abstract : We report the fabrication and performance evaluation of cost-effective, reproducible silver nanodendrite (AgND) substrates, possessing high-density trunks and branches, achieved by a simple electroless etching process and subsequently utilized them for the trace detection of 1, 3, 5-trinitroperhydro-1, 3, 5-triazine (Research Development Explosive, RDX) and Ammonium Nitrate (AN). The intricate structural features in AgNDs offer high-density hotspots for effective molecular detection based on the surface enhanced Raman scattering (SERS) technique. The active SERS-substrate was initially tested with standard Rhodamine 6G (R6G) molecules at 1 nM concentration, which established an effective enhancement factor (EF) of ∼10 8 . The AgNDs were subsequently utilized in the detection of the explosives RDX and AN, down to concentrations of 1 μM. The typical EF achieved in the case of RDX and AN was ∼10 4 . The sensitivity of 1 μM R6G was further enhanced by two-fold through the deposition of Au nanoparticles on the AgNDs. The reproducibility of the low-cost substrate was also demonstrated, with a ∼9% RSD value in the measurements.